Immunomodulatory potential of sugar beet (beta vulgaris) against coccidiosis in broiler chickens - Asghar ABBAS; Kashif HUSSAIN; Muhammad Tahir ALEEM; Sugiharto SUGIHARTO; Houhui SONG; Mohammed M. MARES (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Recent research reports the immunomodulatory capability of Beta vulgaris extract against coccidiosis disease in broiler chickens. Immunomodulatory potential of medicinal plant was evaluated by in vivo trial. For this purpose, broiler chicks (n=175) were alienated into five groups. At one week of age chicks all groups were orally infected with parasite (oocysts) of mixed Eimeria species. At same age group, A, B and C were cured with Beta vulgaris extract at three doses (100, 200 and 300 mg/kg) of body weight. Group D was treated with Vitamin E and served as positive control and Group E was treated with PBS and served as negative control groups. Cellular Immune response was inquired through four classical assays including Dinitrochlorobenzene (DNCB), PHA-P, CON-A and Carbon Clearance test. Humoral immunity (antibodies levels) was evaluated by hemagglutination test. Results of study showed that B. vulgaris extract treated groups showed maximum immune response in terms of increasing both cellular and humoral immunity against Eimeria parasite. However, the immunomodulatory response of groups cured with Beta vulgaris at 300 mg/kg of body weight was higher (P<0.05) as compared to negative control group.